The Chicago Fed DSGE model: Version 2 - Jeffrey R. Campbell; Filippo Ferroni; Jonas D. M. Fisher; Leonardo Melosi (Federal Reserve Bank of Chicago, 2023)
The Chicago Fed dynamic stochastic general equilibrium (DSGE) model is used for policy analysis and forecasting at the Federal Reserve Bank of Chicago. This guide describes its specification, estimation, dynamic characteristics, and how it is used to forecast the U.S. economy. In many respects the model resembles other medium-scale New Keynesian frameworks, but there are several features which distinguish it: the monetary policy rule includes anticipated future deviations, productivity is driven by both neutral and investment specific technical change, multiple price and wage indices identify price and wage inflation, the data are measured in a model consistent way, and market-expected interest rates are used to measure the expected path of the federal funds rate that is taken into account by the model's agents when they make their decisions. The model also incorporates a new method introduced by Ferroni, Fisher, and Melosi (2023) to address the unusual Covid pandemic macroeconomic dynamics.
Keywords: E1; E2; E3; E4; E5; 330; New Keynesian model; DSGE models; Covid-19; pandemic; Survey of Professional Forecasters; business cycles; forecasting; policy analysis